Associations between menstrual cycle and hormonal contraception with satiety hormones and food intake - Löfberg, Ida (2020)
Introduction. The ovarian steroid hormones estradiol and progesterone are potentially capable of affecting dietary intake, which is supported by the vast evidence showing that food intake peaks during the luteal phase and reaches its nadir at ovulation (Hirschberg et al. 2012). Appetite-regulating hormones leptin, ghrelin, and insulin, referred to as satiety hormones, may have interactions with estradiol and progesterone (Budak et al. 2006; Klok et al. 2007; Hirschberg 2012). The objective of this study was to investigate fluctuations in food intake and satiety hormones across the menstrual cycle or hormonal contraceptive use. Methods. 25 women, of whom 16 had never used hormonal contraception (N-group, age 26.2±4.4, BMI 66.6±6.9) and 9 had used hormonal contraception at least one year (H-group, age 22.9±2.4, BMI 19.6±2.9), enrolled in the present study. Data related to dietary intake and cravings were collected with 3-day prospective food record over four phases of the menstrual cycle or hormonal contraceptive use, along with venous blood samples and body composition measurements. Phases of the menstrual cycle were determined by combining counting method with the detection of luteinizing hormone surge in urine (De Jonge 2019). Results. There were no differences in energy or macronutrient intake or cravings between the phases of the menstrual cycle or hormonal contraceptive use. In the N-group. leptin was significantly higher at ovulation and during the luteal phase compared to the menstrual phase and the follicular phase (p<0.05*). In both groups, cravings were reported more in those subjects with higher progesterone levels during the follicular phase or the withdrawal bleeding. Progesterone was positively associated with energy intake in the H-group during the second active phase (r=0.68, p < 0.05). Strong negative correlations were observed between leptin and protein intake during the luteal phase (r=-0.71, p < 0.01), and insulin and protein intake at ovulation (r=-0.74, p < 0.01). Conclusions. Findings of the present study do not support the hypothesis of changing dietary intake across the menstrual cycle in recreationally active athletic women. Progesterone might contribute to higher prevalence of cravings, regardless of hormonal contraceptive use. Higher leptin during the latter half of the menstrual cycle may predict the optimal functioning of hypothalamic-pituitary-ovarian axis, and thereby, eumenorrhea. Given that the regulation of appetite and cyclical hormonal variations are influenced by the interaction of multiple factors, further research with multidisciplinary approach is warranted.